Traffic Potential Evaluation of the Regions in the Context of Rail Passenger Transport – A Case for Slovak Republic - Dedík, Milan; Šperka, Adrián; Čamaj, Juraj; Zábovská, Katarína (Promet - Traffic&Transportation, 2022)
The contribution includes the necessity to analyse the potential of the regions in terms of rail passenger transport. The main research goal is to propose a new concept of determination and evaluation of the particu-lar factors, which evaluate the region potential. Several research methods are used in research, for example the brainstorming methods, methods of expert estimate, and especially point evaluation method. Firstly, the factors influencing the traffic potential are defined and exam-ined. Secondly, specific ways of monitoring and evaluat-ing particular factors are proposed. The research results form the basis of a new methodology for traffic potential determination in regions. Subsequently the mentioned methodology is applied in practice to the selected region-al railway line in Slovak Republic. The potential of this region is expressed by coefficient values of the chosen factors. For example, coefficient of the number of inhab-itants is 2.69 and the average value of the adjacent co-efficient of the railway stations and stops availability is 1.92. The details are explained in the fourth chapter. The proposals and outputs including practical application represent a new innovative way for region evaluation which has so far not been used anywhere. It can help plan and organise traffic service in the regions.